Effect of processing conditions on the thermal and electrical conductivity of poly (butylene terephthalate) nanocomposites prepared via ring-opening polymerization. (5th April 2017) - Colonna, S.; Bernal, M.M.; Gavoci, G.; Gomez, J.; Novara, C.; Saracco, G.; Fina, A.
Abstract: Successful preparation of polymer nanocomposites, exploiting graphene-related materials, via melt mixing technology requires precise design, optimization and control of processing. In the present work, the effect of different processing parameters during the preparation of poly (butylene terephthalate) nanocomposites, through ring-opening polymerization of cyclic butylene terephthalate in presence of graphite nanoplatelets (GNP), was thoroughly addressed. Processing temperature (240 °C or 260 °C), extrusion time (5 or 10 min) and shear rate (50 or 100 rpm) were varied by means of a full factorial design of experiment approach, leading to the preparation of polybutylene terephthalate/GNP nanocomposite in 8 different processing conditions. Morphology and quality of GNP were investigated by means of electron microscopy, X-ray photoelectron spectroscopy, thermogravimetry and Raman spectroscopy. Molecular weight of the polymer matrix in nanocomposites and nanoflake dispersion were experimentally determined as a function of the different processing conditions. The effect of transformation parameters on electrical and thermal properties was studied by means of electrical and thermal conductivity measurement. Heat and charge transport performance evidenced a clear correlation with the dispersion and fragmentation of the GNP nanoflakes; in particular, gentle processing conditions (low shear rate, short mixing time) turned out to be the most favourable condition to obtain high conductivity values. Graphical abstract: Highlights: Thermally conductive pCBT nanocomposites are prepared by ring-opening polymerization. Careful optimization of processing parameters is mandatory for the preparation of highly conductive nanocomposites. Gentle processing conditions are required to obtain high conductivity values. Heat and charge transport performance are correlated with GNP dispersion and fragmentation.